Use of acoustic energy in the processing of molten aluminium alloys - Puga, Hélder (2013)
During the last years aluminium alloys have been gaining increased acceptance as structural materials in the automotive and aeronautical industries, mainly due to their light weight, good formability and corrosion resistance. However, improvement of mechanical properties is a constant in research activities, either by the development of new alloys or by microstructure manipulation. This presentation focuses a novel effective dynamic methodology to perform microstructural refinement / modification and degassing of light alloys, namely aluminium alloys, by applying acoustic energy to the melts. High intensity acoustic energy significantly improves the microstructure, therefore the mechanical properties of those alloys, avoiding the use of traditional chemically based degassing and refining techniques which are less effective and present significant environmental impact. Ultrasonic (US) vibration has proven to be extremely effective in degassing, controlling columnar dendritic structure, reducing the size of equiaxed grains and, under some conditions, producing globular grains and modifying the eutectic silicon cells in Al-Si alloys. The mechanisms of US processing of aluminium melts are discussed and experimental results on this field are presented.